Escherichia coli survival in plasma‐treated water and in a gas–liquid plasma reactor. Issue 12 (5th August 2020) - Rodriguez, Cesar; Wandell, Robert J.; Zhang, Zhiming; Neurohr, Julie M.; Tang, Youneng; Rhodes, Ryan; Kinsey, Stephen T.; Locke, Bruce R.
Abstract: The effects of post‐plasma exposure to deionized water treated by argon–water plasma and to direct plasma treatment of bacteria in a liquid solution of a strain of Escherichia coli, which was independently evolved to resist the bactericidal effects of hydrogen peroxide, were determined. The hydrogen peroxide resistant phenotype of the evolved strain was proportional to the initial cell density. The catalase activity was significantly elevated in the evolved strain as compared with the wild‐type strain, and the evolved strain resisted the bactericidal effects of plasma‐treated water (post‐plasma exposure) as compared with the wild‐type strain. The evolved strain remained viable after flowing through the plasma reactor and lysed less when exposed to (nonplasma control) hydrogen peroxide solutions as compared with the wild‐type cells. Abstract : Hydrogen peroxide‐resistant Escherichia coli suspended in aqueous solutions can survive exposure to nonthermal plasma generated at the gas–liquid interface as well as to (post) plasma‐treated water. The hydrogen peroxide‐resistant phenotype correlated with increased production of catalase, relative to the wild‐type strain.